Peningkatan Kemandirian dan Mobilisasi Penderita Pasca Stroke melalui Stroke Education Program (SEP) Berbasis Telerehabilitation pada Paguyuban Stroke di Tuban - Syafaah, Nurus; pitaloka, Dyah; Basuki, Hyan Oktodia; Arifin, M. Fahrul (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Background: Stroke is a neurological disorder that occurs due to disruption of blood circulation to the brain which lasts for about 24 hours or more. The activities of the stroke association are running quite smoothly, but some programs are not running well, especially the program to move the body using physical or movement techniques. Lack of knowledge and awareness of sufferers to practice moving their stiff bodies. This causes the condition of stroke sufferers to worsen. Method: This education is provided to provide an overview of stroke and its prevention, both for families who provide support and care and for sufferers themselves to provide encouragement and an overview of what activities they must carry out correctly. Providing the SEP stroke education program using the telerehabilitation method is very appropriate for patients to use while at home to control and as telerehabilitation which can be used for rehabilitation patients at home to increase independence and mobility in post-stroke patients. Results: The stroke education activities of the SEP program using the telerehabilitation method have shown significant results with the evaluation results of stroke sufferers having a lot of improvement in their abilities, especially in independence and re-mobilization. Conclusion: This community service activity is a means of helping post-stroke patients to be able to control and act as home rehabilitation aids to increase independence and mobility in post-stroke patients and also answer the challenges of the 5.0 era.